Portraits of a mature God : choices in Old Testament theology - McEntire, Mark Harold, 1960- (Fortress Press, 2013)
"What difference would it make for Old Testament theology if we turned our attention from the more dramatic, forceful "mighty acts of God" to the more subdued, but more realistic themes of later writings in the Hebrew Bible? The result, Mark McEntire argues, would be a more mature theology that would enable us to respond more realistically and creatively to the unprecedented challenges of the present age."--